Adjective word group and its types - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article is devoted to the changes in the meanings of post-nominative adjectives in the process of transformation in contemprorary English. In English, adjectives can act as a predicate. The semantics of adjectives, which carry a predicative function, is characterized by internal qualitative diversity. Qualitative adjectives mainly refer to the classical predicate and directly indicate the attribute of the subject. Such adjectives have more predicative features. The predicative feature of the adjective, the presence of the connotation of subjective evaluation determine both its semantics and use. The development from a special sign of thought to a general concept is characteristic of the entire structure of the English language, it is even possible to observe this in word formation. In most cases, taking into account the use of the adjective in the function of definition, the terms postpositive (postnominative) and prepositive (prenominative) adjectives are used.